Re-engineering grassroot sports for improved social inclusion and transformational development (2019)
Grassroot sports have shown to be pre-requites lo outstanding and excellent performance which can be used for community development and societal transformation. Grassroot sports development in Nigeria is given little or no concerns today as this affect national development of youths where many social vices are on the increase and the performance of Nigeria at various international sporting competitions has reduced drastically compared lo the past. Sport serves as a tool that unites people together irrespective of race, ethnicity, group, age, social status, education level and also contributes to the overall economic and political development. This paper therefore examined re-engineering grassroot sports for improved social inclusion and transformational development of a nation. Also, the paper examined concept of grassroot sport, growth and development, institutional sports, characteristics and benefits of sport, grassroot sports for social inclusion and transformational development. The authors recommend refocus the priorities of the sports policies to highlight the contribution of sport to achieving the objectives of other policies, including those on health, social cohesion, education, youth, non- discrimination, and the reception and integration of migrants